On the Completely Positive and Positive Semidefinite-Preserving Cones—Part III. (23rd May 2012) - Klimas, Andrew J.; Hill, Richard D.
Abstract : This paper studies the extremals and other faces of the completely positive and positive semidefinite-preserving linear transformations.